2015
DOI: 10.1185/03007995.2015.1053048
|View full text |Cite
|
Sign up to set email alerts
|

Meta-analysis of studies examining medication adherence, persistence, and discontinuation of oral antihyperglycemic agents in type 2 diabetes

Abstract: The results of the analysis demonstrate that medication adherence, persistence, and discontinuation rates are suboptimal in patients with T2DM prescribed OAHAs.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

9
99
1
5

Year Published

2017
2017
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 125 publications
(114 citation statements)
references
References 44 publications
9
99
1
5
Order By: Relevance
“…For instance, a recent meta-analysis conducted by Iglay et al (2015) found that daily diabetes medication adherence (MPR) was 75.3% in the general population (Iglay et al, 2015); which is only slightly less than the 77.3% adherence we observed in the schizophrenia population. This is also the case when comparing these findings to other reviews of diabetes medication adherence in the general population.…”
Section: Diabetes Medication Adherence In Schizophrenia 23contrasting
confidence: 57%
“…For instance, a recent meta-analysis conducted by Iglay et al (2015) found that daily diabetes medication adherence (MPR) was 75.3% in the general population (Iglay et al, 2015); which is only slightly less than the 77.3% adherence we observed in the schizophrenia population. This is also the case when comparing these findings to other reviews of diabetes medication adherence in the general population.…”
Section: Diabetes Medication Adherence In Schizophrenia 23contrasting
confidence: 57%
“…This could explain the higher MPR across all groups in our study as compared with that in previous studies. [17,19,23] …”
Section: Discussionmentioning
confidence: 99%
“…For example, a meta-analysis of 27 studies that evaluated adherence rates to T2DM medications found that only 22% of studies reported ≥80% adherence among patients 6. A systematic review of observational studies reporting persistence with oral antidiabetes drugs (OADs) in patients with T2DM revealed a mean rate of 56.2%, with discontinuation estimates of 31.4% 7. Similarly, using claims data, rates of insulin glargine persistence in the first year after initiation of ~55.0% were reported 8,9.…”
Section: Introductionmentioning
confidence: 99%